Sex-steroids and social network in relation to Staphylococcus aureus nasal carriage - Stensen, Dina Benedicte Berg (UiT The Arctic University of Norway, 2022)
Staphylococcus aureus ( S. aureus ) is a human pathogen that can colonize skin and mucosa. Nasal carriage is associated with increased risk of autoinfection and transmission and it is therefore important to identify possible targets for prevention of carriage. Sex and age are the most important risk factors for S. aureus carriage, and hypotheses about sex-steroids as major host determinants have therefore emerged. We investigated if hormonal contraceptives and endogenous sex-steroids were associated with S. aureus carriage. We studied the transmission of S. aureus carriage in social networks and examined if known host risk factors for carriage were associated with social contact, indicating potential confounding or indirect transmission. We used data from the cross-sectional health surveys Fit Futures 1&2 and the sixth Tromsø Study. Females taking combination hormonal contraceptives (containing both estrogen and progestin) had doubled odds of nasal carriage compared to non-users. Users of progestin-only contraceptives had half the odds of nasal carriage compared to non-users. An increase in endogenous testosterone in women gave reduced odds of S. aureus nasal carriage. We found similar associations in adult men, but data were inconclusive. We demonstrate transmission of S. aureus and specific S. aureus genotypes in a social network of youths. We found higher risk of transmission with female friendships, while male friendships had no influence on transmission, although men were more frequent carriers. Use of alcohol more than twice a month, normal BMI, and moderate/high physical activity were associated with transmission. The results suggest that both exogenous and endogenous sex-steroid exposures are relevant in carriage of S. aureus . We show for the first time that the male predominance in carriage is determined by sex-specific predisposing host characteristics as S. aureus social transmission is less frequent than in females. We need more prospective studies to clarify causal relationships and targets for ...